Bone Augmentation in Oral Implantology: A Systematic Review - Sura A. A. Fuoad Al-Bayati; M Sesha Reddy; Digpal Rana; Daya Srinivasan; K. A Shanmugaavel; C Pradeep (Journal of Pharmacy and Bioallied Sciences, 2025)
Introduction: Implant dentistry has significantly advanced, offering effective solutions for tooth loss. This review aims to evaluate recent research on various techniques and materials used in implant dentistry, focusing on short implants, bone augmentation, sinus lift procedures, and soft tissue management. Methods: A systematic review of relevant literature was conducted using PubMed and Google Scholar. Studies were included based on predefined inclusion and exclusion criteria. Data extraction was performed to identify key findings related to treatment outcomes, complications, and patient satisfaction. Results: Short implants offer a viable alternative to bone augmentation, with fewer complications. Bone graft materials promote regeneration, and sinus lift techniques offer advantages and limitations. Soft tissue management is crucial for optimal outcomes. Conclusion: Advancements in implant dentistry include short implants and bone graft materials, but further research is needed for optimal treatment protocols, patient selection, surgical technique, and postoperative care.